Physical interventions for preventing stress fractures of the lower limbs - Dubois, Blaise (Cochrane Database Syst Rev, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects (benefits and harms) of different physical interventions for preventing stress fractures of bone of the lower limbs. The focus will be on physically active individuals aged between adolescence and early middle age.